2020
DOI: 10.21500/19002386.4851
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar emocional, psicológico y social en adultos argentinos en contexto de pandemia por COVID-19

Abstract: El objetivo del presente trabajo fue determinar el bienestar emocional, psicológico y social en adultos argentinos en contexto de pandemia por COVID-19. El diseño metodológico utilizado fue no experimental de corte transversal, bajo la modalidad de estudio descriptivo y de diferencia de grupos. Se trabajó con una muestra de 888 participantes, residentes en diferentes provincias de Argentina, de edades comprendidas de entre 18 y 84 años (MEDAD = 36.98; DE= 15.37; 51.2 % mujeres, 48.8 % varones). Los resultados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
1
7
0
2
Order By: Relevance
“…In the case of this study, conducted between May and August 2020, it was identified that 60.9% of the participants had psychological distress. Thus, when considering that various studies on the impact of lockdown by epidemics place the prevalence of distress between 20% and 57%, [ 8 , 10 ] it is observed that, in the present study sample, there was greater psychological vulnerability, being the results consistent with what was reported in different national [ 5 , 17 – 19 ] and international studies. [ 6 , 7 , 11 , 12 , 15 , 23 ] In addition, the reported percentage shows that levels of psychological distress during the COVID-19 pandemic remained above prevalence rates for symptoms and use of mental health services in Argentina.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the case of this study, conducted between May and August 2020, it was identified that 60.9% of the participants had psychological distress. Thus, when considering that various studies on the impact of lockdown by epidemics place the prevalence of distress between 20% and 57%, [ 8 , 10 ] it is observed that, in the present study sample, there was greater psychological vulnerability, being the results consistent with what was reported in different national [ 5 , 17 – 19 ] and international studies. [ 6 , 7 , 11 , 12 , 15 , 23 ] In addition, the reported percentage shows that levels of psychological distress during the COVID-19 pandemic remained above prevalence rates for symptoms and use of mental health services in Argentina.…”
Section: Discussionsupporting
confidence: 91%
“…This can be understood in the light of other studies [ 7 , 8 , 10 , 17 , 18 ] which showed that having children and living with a partner or family member operate as factors of well-being or perception of less discomfort, while living alone or having a non-cohabiting partner would become factors of psychological distress. The differences with the study by Eidman et al [ 5 ] could be due both to the difference in the methodological approach and in the conceptualization of psychological variables.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Es imprescindible que se continúen desarrollado estudios de carácter similar, pues de momento los estudios al respecto suelen estar enfocados en la emergencia sanitaria y problemas de salud de la COVID-19 (47), sin enfocarse necesariamente en el aspecto de desgaste psicosocial que esta enfermedad conlleva, ya que la "curva viral" tiende a eclipsar la importancia de la salud mental. Los prejuicios y los discursos homogeneizadores con que se suele tratar a los adultos mayores tampoco colaboran en estos tiempos de pandemia (48), y estos también indican que este grupo etario requiere de modelos y formas de aproximación específicas, en especial en situaciones de pandemia que son la oportunidad para plantear nuevos marcos de atención integral para los adultos mayores antes no existentes (49,50).…”
Section: Discussionunclassified
“…Posteriormente se aplicó una investigación descriptiva porque en los resultados se describen las características de la muestra de estudio (familias del barrio la pradera de Ambato-Ecuador), lo cual nos ha ayudado en la recolección de la información referente al bienestar psicológico y los efectos producidos por la pandemia Covid-19. Por otra parte, se realizó una investigación explicativa para dar a conocer el fenómeno objeto de estudio en nuestro caso explicar concordamos con Eidman et al (2020), al estudiar los efectos que se está produciendo por la actual pandemia en el bienestar psicológico, emocional y social de las familias.…”
Section: Metodologíaunclassified